A REVIEW OF THE USE OF CALCIUM LIQUID VERSUS CALCIUM TABLETS FOR MAINTAINING CORRECTED CALCIUM LEVELS. Issue 9 (17th August 2016) - Semple, Diarmaid; Howlett, Moninne
Abstract : Aim: Since the discontinuation of a commercially available liquid calcium medicine, there have been various local strategies to obtain adequate calcium levels, particularly in suspected 22Q11.2 deletion syndrome children post cardiothoracic surgery. Pharmacy obtained on special order a Calcium Liquid food supplement (0.5 mmol calcium/ml) for use in those children whom effervescent tablets did not appear to improve corrected calcium. Anecdotally it was thought that calcium liquid was better tolerated and absorbed, resulting in quicker recovery time of corrected calcium than use of the effervescent tablets. This review of patients was intended to determine if the use of the liquid was associated with a significant improvement in calcium levels compared to the use of tablets. Method: A dispense report was undertaken to identify those patients supplied with the calcium liquid product from May 2014 to May 2015. Using the electronic prescribing system, the patients electronic health record was accessed, and the following information recorded; calcium, albumin, intake calcium in fluids, TPN, oral and Intravenous. The data was collected for seven days previous to the first administration of calcium liquid and seven days after where available. Corrected calcium was calculated using an accepted method (calcium=serum calcium+0.02* (normal albumin – patient albumin)). Results: Nine children supplied with calcium liquid between May 2014 and May 2015. Four patients who did not have histories on the electronic prescribing system were excluded for ease of analysis. The electronic medication record of the five remaining patients was used to compare calcium intake from all sources including fluids and feed. As expected calcium levels (and corrected calcium level where relevant) did improve when calcium liquid was added in. However four of the patients received calcium from multiple sources. Of these three received more calcium (mmol/kg/day) in fluids and feeds than from the administered pharmacy product. One single patient did not receive calcium from any other sources (fluids/TPN/feed). However there did not appear to be a significant change in calcium levels when calcium liquid was introduced as opposed to calcium tablets. Conclusion: Although based on a small number of patients, from this experience it would not seem that the calcium liquid obtained by pharmacy results in higher calcium serum levels. Further analysis may be required to distinguish the effects from calcium intake in feed/fluid and calcium intake from medicines.